Three-Dimensionally Printed Ti2448 With Low Stiffness Enhanced Angiogenesis and Osteogenesis by Regulating Macrophage Polarization via Piezo1/YAP Signaling Axis - Tang, Zhen; Wei, Xinghui; Li, Tian; Wu, Hao; Xiao, Xin; Hao, Yulin; Li, Shujun; Hou, Wentao; Shi, Lei; Li, Xiaokang; Guo, Zheng (Frontiers in Cell and Developmental Biology, 2021)
Previous studies have found that the novel low-elastic-modulus Ti2448 alloy can significantly reduce stress shielding and contribute to better bone repair than the conventional Ti6Al4V alloy. In this study, the promotion of osteogenesis and angiogenesis by three-dimensionally printed Ti2448 were also observed in vivo. However, these were not significant in a series of in vitro tests. The stiffness of materials has been reported to greatly affect the response of macrophages, and the immunological regulation mediated by macrophages directly determines the fate of bone implants. Therefore, we designed more experiments to explore the role of three-dimensionally printed Ti2448 in macrophage activation and related osteogenesis and angiogenesis. As expected, we found a significant increase in the number of M2 macrophages around Ti2448 implants, as well as better osteogenesis and angiogenesis in vivo. In vitro studies also showed that macrophages pre-treated with Ti2448 alloy significantly promoted angiogenesis and osteogenic differentiation through increased PDGF-BB and BMP-2 secretion, and the polarization of M2 macrophages was enhanced. We deduced that Ti2448 promotes angiogenesis and osteogenesis through Piezo1/YAP signaling axis-mediated macrophage polarization and related cytokine secretion. This research might provide insight into the biological properties of Ti2448 and provide a powerful theoretical supplement for the future application of three-dimensionally printed Ti2448 implants in orthopaedic surgery.